Beyond Borders: The Accelerating Momentum of Domestic Violence Research Worldwide - Neupane, Dasarath; Lourdusamy, Arputhem (NPRC Journal of Multidisciplinary Research, 2024)
This paper covers publication trends, co-author networks, and research keyword co-occurrences on academic research related to domestic violence between 2000 and 2023. Throughout these years, first, the number of published articles dealing with this topic was very limited, from just four articles in the year 2000 to 37 in 2013. Still, after an imposing surge in publications registered after 2013, particularly between 2020 and 2023, the numbers increased from 217 to 653, establishing a significantly increased impact on the reviewed issue at a global level. This network identifies some central figures in the research community, such as Gene Feder, Louise M. Howard, and Nicky Stanley among others. It underlines the existence of collaboration clusters around issues such as gender, domestic violence, mental health, and social work, hence emphasizing the very essence of interdisciplinary research. Through keyword co-occurrence analysis, the word cloud shows some central themes to include intimate partner violence and the effect of COVID-19 on different population focuses, including strong qualitative research methods. The second word cloud, that of author affiliation, demonstrates the concentration of research output by leading institutions, with a high volume emanating from the UK, but also global collaboration - significant contributions from universities in Australia being one of them. Domestic violence is a complicated issue that affects individuals and communities of all ages, genders, sexual orientations, educational backgrounds, and more. These terminological complications in defining domestic violence can result in confusion during the practice of identification, assessment, and intervention. This study follows a holistic approach to bibliometrics in reviewing scholarly literature on domestic violence by drawing on data from Lens.org along with the visualization tools of VOSviewer. Improvement in understanding the domestic violence research landscape, major contributors, collaboration patterns, and the gap in research is what this study attempts to address. A total of 92,443 documents in their study were filtered to 2,362 scholarly works that included research articles published from 1999 up to 2023. The findings indicate the important factors of institutions and countries, the necessity of interdisciplinary-wise collaboration, and emerging hotspots of research. A bibliometric approach emphasizes that for effective intervention and prevention, there is a need for systematic reviews and synthesis of the available literature to provide informed evidence-based policy and practice in the context of domestic violence.